PENGARUH DAUN PEPAYA TERHADAP KECUKUPAN ASI PADA IBU NIFAS DIKLINIK CITRA MARENDAL - Nurul Aini Siagian (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
This study aims to determine the characteristics of respondents where there is sufficient breast milk in postpartum mothers at clinic Citra Marindal. To determine the effect of providing adequate breast milk before being given papaya leaves at clinic Citra Marindal. To find out there is an effect of sufficient breast milk after being given papaya leaves at clinic Citra Marindal. To find out the effect of giving papaya leaves to breast milk adequacy in clinic Citra Marindal. This type of research is a type of quantitative research. This type of quantitative research is research by obtaining data in the form of numbers or qualitative numbers. The population observed by the researchers in this study were all post partum mothers in clinic Citra Marindal, as many as 15 respondents. Univariate analysis and bivariate analysis. The results of the research data before being given papaya leaves showed that the respondents' characteristics were sufficient, namely 6 people (40%) and the results of the respondents' characteristics were less, namely 9 people (60%). Based on the data after being given papaya leaves, the results of the characteristics of the respondents were Good, namely as many as 4 respondents (26.7%) and the results of the characteristics of respondents were Enough, namely as many as 11 people (73.3%). The results of the Wilcoxon statistical test on the effect of papaya leaves on the adequacy of breast milk in postpartum mothers obtained the results of p value (.000) < (0.002), then Ha accepted Ho was rejected and it could be concluded that there was an effect of papaya leaves on the adequacy of breast milk in postpartum mothers.